2009
DOI: 10.1186/1471-213x-9-26
|View full text |Cite
|
Sign up to set email alerts
|

Adenomatous polyposis coli-mediated control of β-catenin is essential for both chondrogenic and osteogenic differentiation of skeletal precursors

Abstract: Background: During skeletogenesis, protein levels of β-catenin in the canonical Wnt signaling pathway determine lineage commitment of skeletal precursor cells to osteoblasts and chondrocytes. Adenomatous polyposis coli (Apc) is a key controller of β-catenin turnover by down-regulating intracellular levels of β-catenin.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
38
0

Year Published

2010
2010
2018
2018

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 51 publications
(41 citation statements)
references
References 51 publications
3
38
0
Order By: Relevance
“…(30)(31)(32)(33)(34) Using murine conditional genetic models, we and others have shown that Apc is involved in the regulation of both prenatal and postnatal bone mass accrual by regulating the levels of Wnt/b-catenin signalling. (11,12) This study confirms findings from these in vivo animal studies by demonstrating that heterozygous mutations in the APC gene are associated with a higher than normal bone mass in a majority of FAP patients.…”
Section: Discussionsupporting
confidence: 84%
See 2 more Smart Citations
“…(30)(31)(32)(33)(34) Using murine conditional genetic models, we and others have shown that Apc is involved in the regulation of both prenatal and postnatal bone mass accrual by regulating the levels of Wnt/b-catenin signalling. (11,12) This study confirms findings from these in vivo animal studies by demonstrating that heterozygous mutations in the APC gene are associated with a higher than normal bone mass in a majority of FAP patients.…”
Section: Discussionsupporting
confidence: 84%
“…Which particular APC mutation has the most beneficial effect on BMD thus remains to be elucidated. As observed in conditional heterozygous Apc mutant mice, (11,12) FAP patients display an average height similar to that of the general population, suggesting that one functional APC allele is sufficient for normal longitudinal bone growth.…”
Section: Discussionmentioning
confidence: 68%
See 1 more Smart Citation
“…Interestingly, no quantifiable differences were observed in proliferation or density during in vitro osteoblast differentiation. Deletion of APC via the Col2aI-driven Cre promoter resulted in impaired skeletogenesis due to the inability of chondrocytes and osteoblasts to terminally differentiate (133). From these data, it is clear that the role of APC in regulating β-catenin activity is crucial for both cell autonomous and intercellular regulation of skeletal cell types.…”
Section: Adenomatous Polyposis Coli (Apc)mentioning
confidence: 80%
“…Amhr2Cre mice were bred with Rosa26 reporter mice (Soriano, 1999) to review Cre expression, and were bred with Apc 15lox mice (Miclea et al, 2009;Robanus-Maandag et al, 2010) to obtain Apc 15flox/15flox mice ("flox" means that the sequence between two loxP sites has been deleted by Cre). PgrCre animals (Soyal et al, 2005) …”
Section: Animals and Genotypingmentioning
confidence: 99%